2013
DOI: 10.1037/a0030566
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of discussing suicide with Alaska native college students: Qualitative analysis of in-depth interviews.

Abstract: Suicide represents a significant health disparity for communities in rural Alaska, and has implications for mental health among people who have lost loved ones from suicide. A qualitative interview study was conducted to examine the ways in which suicide has affected the lives of college students who have migrated from rural villages to an urban university (N = 25). The present research represents a secondary aim of the study-specifically, we examined the affective responses of Alaska Native college students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…40 For many it may be the first opportunity to talk about their loss, 33 which is particularly relevant in cultures where people are expected to grieve silently and remain stoic. 41 No distress was reported by participants as a result of the interviews in the current study, which adds weight to the emerging body of evidence that suggests participation in research does not necessarily lead to distress, 19,29,33,39 and supports the challenge to members of IRBs and HRECs to review their guidelines and decision-making processes on the issues, risks, and benefits surrounding bereavement research. 42 Some participants in the current study specified that they would prefer to participate in an interview after some time had passed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…40 For many it may be the first opportunity to talk about their loss, 33 which is particularly relevant in cultures where people are expected to grieve silently and remain stoic. 41 No distress was reported by participants as a result of the interviews in the current study, which adds weight to the emerging body of evidence that suggests participation in research does not necessarily lead to distress, 19,29,33,39 and supports the challenge to members of IRBs and HRECs to review their guidelines and decision-making processes on the issues, risks, and benefits surrounding bereavement research. 42 Some participants in the current study specified that they would prefer to participate in an interview after some time had passed.…”
Section: Discussionsupporting
confidence: 52%
“…For a few participants, having the opportunity to talk was helpful, supporting findings that the bereaved often experience interview participation as positive. 20,21,33,39 Participants in a psychological autopsy interview in Central Northern Uganda expressed that the interview helped their personal growth, had a therapeutic effect, encouraged participant empowerment, and afforded a safe opportunity for expression. 40 For many it may be the first opportunity to talk about their loss, 33 which is particularly relevant in cultures where people are expected to grieve silently and remain stoic.…”
Section: Discussionmentioning
confidence: 99%
“…DeCou et al ( 37 ) conclude that discussing the issue of suicide can be an important aspect of suicide prevention for Alaska Native university students, who are survivors of suicide in their communities. They mention that their findings could also offer some assistance to help mitigate concerns raised by research ethics boards over asking questions about suicide during interview research, as they found that actually speaking about suicide had positive benefits for the person being interviewed ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the far-reaching impact of suicide in rural Alaska and ethical concerns related to asking participants about their personal experiences related to suicide, the study included a safety plan to address participant distress and provided a list of crisis counselling resources to all participants. However, it is important to note that there were no adverse reactions among participants in the interview study; the safety plan was not needed, and participants reported their experiences to be meaningful and beneficial, despite being difficult (13). Students were offered $50 as compensation for their time and effort.…”
Section: Methodsmentioning
confidence: 99%